Getting the best out of supervision in counselling and psychotherapy : a guide for the supervisee - Creaner, Mary (Los Angeles ; London ; New Delhi ; Singapore ; Washington, DC : SAGE, 2014)
"Supervision is an essential part of counselling training and ensuring you know exactly how to get the very most out of supervision is important, whatever your level of study. Exploring how to begin, maintain and end a supervisory learning relationship in the context of existing theory and best practice guidelines, the author will introduce your trainees to: Models and forms of supervision ; The skills informing good supervision ; What to expect from supervision ; Key professional issues in supervision. Written in a lively and engaging style, this book will enable both supervisors and supervisees to get the best they can from the supervisory experience." -- cover.
What is the meaning and purpose of supervision? -- The supervisory relationship: a relationship with a purpose -- Supervision across the career lifespan -- The learning landscape: lifelong learning in supervision -- Models and frameworks of supervision -- Forms and formats of supervision -- Beginning the learning relationship -- How to prepare for a supervision session -- Ethical and legal considerations in supervision -- Good and not so good supervision -- Professional considerations in supervision -- Feedback and evaluation in supervision -- Endings in the learning relationship and the opportunities ahead -- Developing the art and science of supervision.
Includes bibliographical references (pages 144-164) and index.
Text in English.
Keywords: Counseling; Psychotherapy; Supervision; Supervision of employees; Counselors -- Supervision of; Counseling; Counselors -- Supervision of; Psychotherapy; Supervision; Supervision of employees; Society